2022
DOI: 10.3390/life12091399
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Micro-, Lunar, and Martian Gravities on Earth—Effects on Escherichia coli Growth, Phenotype, and Sensitivity to Antibiotics

Abstract: Bacterial behavior has been studied under microgravity conditions, but very little is known about it under lunar and Martian gravitational regimes. An Earth-based approach was designed and implemented using inclined clinostats and an in-house-developed code to determine the optimal clinorotation angular speed for bacterial liquid cultures of 5 RPM. With this setup, growth dynamics, phenotypic changes, and sensitivity to antibiotics (minimum inhibitory concentration (MIC) of two different classes of antibiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In the event of an S. aureus infection, antibiotics are commonly administered as a form of treatment strategy. Whilst studies on the ISS have shown the inhibition of gentamicin efficacy [ 27 , 37 , 38 ], our results showed that gentamicin under the simulated microgravity conditions achieves a 4.8 ± 2.05 (OD600)-fold decrease compared to no gentamicin, whereas, under Earth’s gravity conditions, gentamicin achieves a 6.24 ± 2.53-fold decrease compared to no gentamicin. Thereby, gentamicin is contributing to the inhibition of S. aureus proliferation under both tested conditions.…”
Section: Discussionmentioning
confidence: 52%
“…In the event of an S. aureus infection, antibiotics are commonly administered as a form of treatment strategy. Whilst studies on the ISS have shown the inhibition of gentamicin efficacy [ 27 , 37 , 38 ], our results showed that gentamicin under the simulated microgravity conditions achieves a 4.8 ± 2.05 (OD600)-fold decrease compared to no gentamicin, whereas, under Earth’s gravity conditions, gentamicin achieves a 6.24 ± 2.53-fold decrease compared to no gentamicin. Thereby, gentamicin is contributing to the inhibition of S. aureus proliferation under both tested conditions.…”
Section: Discussionmentioning
confidence: 52%
“…Rotating Wall Vessels (RWV) operate under the assumption that they provide a similar fluid environment to that of true microgravity by ensuring that cells travel in small circular paths that stay within their depletion zones ( Hammond and Hammond, 2001 ; Klaus, 2001 ). Our results may be paired with calculations estimating the path traveled by microbial cells in RWVs ( Allen et al, 2022 ) to aid in experimental design for future ground-based microgravity research.…”
Section: Discussionmentioning
confidence: 99%
“…Rotating Wall Vessels (RWVs), devices typically used to simulate microgravity for ground-based microbiology experiments, are designed to mimic the quiescent environment of microgravity by balancing forces to keep cells within their zone of depletion ( Hammond and Hammond, 2001 ; Klaus, 2001 ). RWVs are a form of clinostat rotating in a 2-dimensional plane, and many forms have been used in experiments, including both deep cylindrical ( Allen et al, 2022 ) and shallow wide ( Chao and Das, 2015 ) devices. (Other microgravity simulation devices, such as 3D clinostats and random positioning machines, involve more complex fluid dynamics and are not discussed here ( Wuest et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gravity is contrasted throughout the entire culture process Excessive magnetic field or magnetic culture medium may influence the biological process of cells is feasible to tilt the clinostat or develop a program to determine the appropriate angular velocity. [29] The clinostat is widely used in the study of simulating microgravity because of its simplicity and availability. [24] It has been reported that 2D clinostat was used to simulate a microgravity environment for cultured human umbilical vein endothelial cells and explore the potential mechanism of mitogen-induced phagocytosis.…”
Section: Magnetic Buoyancy Counteracts Gravitymentioning
confidence: 99%
“…[ 28 ] In addition, to better simulate the required microgravity environment, it is feasible to tilt the clinostat or develop a program to determine the appropriate angular velocity. [ 29 ]…”
Section: Simulated‐microgravity Bioreactorsmentioning
confidence: 99%